Evolution of a Strategy for Concise Enantioselective Total Synthesis of the Salinosporamide Family of Natural Products. (2nd September 2022) - Park, Soojun; Lee, Jiwoo; Kim, Jae Hyun; Jeong, Yeji; Lee, Seokwoo; Lee, Su Won; Kim, Sanghee
Abstract: Our first strategy for rapidly accessing pyrrolidinone cores of salinosporamides involved combined use of memory of chirality and dynamic kinetic resolution principles in aldol reactions of the serine‐derived 5‐oxazolidinone substrate, which was ultimately unsuccessful with respect to enantioselectivity. This failure led us to the revised strategy. The influence of the stereocenter in 5‐oxazolidinone enabled selective installation of the C‐2 stereocenter. The intramolecular aldol reaction of the C‐2 stereodefined aldol substrate was successful. An unexpected hydrolytic dynamic kinetic resolution was observed in hydrolyses of the bicyclic aldol products. This unprecedented substrate‐driven hydrolytic dynamic kinetic resolution was utilized in preparing the pyrrolidinone core with excellent efficiency. Through this strategy, the concise total syntheses of salinosporamides A and B as well as cinnabaramides A, E, and F were achieved with high selectivity. Abstract : Described herein are the total syntheses of salinosporamides and cinnabaramides via a strategy involving rapid construction of the highly decorated pyrrolidinone core of the natural products from the simple amino acid serine. The key to the success of this synthesis was to exploit the innate properties of the serine‐derived 5‐oxazolidinone as a stereochemical controller and unprecedented substrate‐driven hydrolytic dynamic kinetic resolution.